Oral epidemiological profile and risk factors in adolescents with different degrees of down syndrome in a vulnerable peruvian rural population - Tipe Bonifaz, Cinthya (2019)
Aim: The aim of this study is to assess the epidemiological profile of 12- to 16-year-old adolescents with Down syndrome in the Special Basic Education Center in Lima—Peru. Materials and methods: A cross-sectional descriptive study was performed, where the epidemiological profile was determined through the DMF-T index, oral hygiene index (OHI), and the gingival index from Silness and Löe. A sample of 107 adolescents with Down syndrome in a Peruvian rural population were considered who were evaluated with the formula of proportion estimation, of which 48 (44.8%) were females and 55 (59%) males. Results: Patients with mild to moderate Down syndrome were with a caries prevalence of 42 and 27.1%, respectively. Likewise, class III malocclusion was present in 42.9 and 25.2%. The most prevalent OHI was the regular category with 66.2%. Conclusion: It was evident in mild Down syndrome adolescents, a higher prevalence of the indexes: dental caries, malocclusion, periodontal disease, and oral hygiene, moderate to severe.